PENGARUH PEMBERIAN EKSTRAK HIPOFISA DAN PROBIOTIK ABG-O PADA ANAK BABI PERSILANGAN TERHADAP PENINGKATAN BERAT BADAN SAPIH, UKURAN LINEAR TUBUH DAN METABOLIT DARAH (The effect of giving pituitary and probiotic extracts abg-o to piglets crosses.....) - Mardemus Misa; Wilmientje M Nalley; Thomas Mata Hine; Twenfosel Dami Dato; Maritje A Hilakore; Mariana Nenobais; Aloysius Marawali (JURNAL NUKLEUS PETERNAKAN, 2020)
The purpose of this study was to determine the effect of giving pituitary extract (EH) and probiotics ABG-O on piglets crossing to increase weaning weight, linear size of body and blood metabolites. The research material was a crossbred of landrace and duroc aged 2 weeks, as many as 24 birds. The experimental design was a completely randomized design with three treatments and eight replications. The three treatments are P0 (control), P1 (EH injection 1 mL), and P2 (injection EH 1 mL + probiotic ABG-O 2 mL). EH injections are carried out every 5 days and administration of probiotics is given orally using spoit every day until the piglets are weaned. The parameters observed were weight gain, linear size of body and blood metabolites. This data was analyzed by ANOVA and continued with Duncan test. The results of this study indicate that the average daily weight gain of crossbred piglets in treatments P0, P1, and P2 are 0.11; 0.13; 016 kg, body length (0.40; 0.45; 0.44 cm), chest circumference (0.29; 0.27; 0,30 cm), and shoulder height (0.25; 0.24; 0.25 cm). Blood glucose levels (117.31; 112.85; 117.25) and total plasma protein (4.60; 4.90; 4.80). The results of the statistical analysis showed that the EH and ABG probiotic treatments affected the UN (P<0.05) but did not affect (P> 0.05) the size of the linear body and blood metabolites. It can be concluded that the administration of pituitary extracts and ABG probiotics can increase the weaning weight but does not affect the linear size of the body blood metabolites and total protein plasma of crossing piglets.